Modulações para a redução da tensão de modo comum em conversores de potência trifásicos - Chaves, Diego Brum (2022)
In recent years, there has been significant growth in the use of alternative energy generation sources, particularly renewable ones. Environmental issues and the cheapness of these new generation sources are factors that justify this growth. Among the new alternatives, the photovoltaic generation was the one that grew the most in the last five years. Among the advantages of photovoltaic generation is the possibility of distributed generation, which reduces the structure of energy distribution and transmission. In addition, with the same purpose of reducing the structure and increasing efficiency, transformerless systems connected to the grid have been the target of industry and academia in several studies. However, in transformerless photovoltaic systems, the common-mode voltage generated by inverters can incite leakage currents. Leakage currents increase overall system losses, interfere with protective devices, reduce the life of photovoltaic panels and other equipment. To prevent this issues, photovoltaic standards have been established stipulating a maximum value for the leakage current. In the literature, there are several techniques to eliminate or reduce leakage currents. Among these, the use of a modified LCL filter (MLCL) is a simple and efficient alternative, since this small modification in the filter considerably increases the attenuation of the leakage current. Additionally, several modulation techniques, which do not require modifications to filters or inverter topology, have been proposed in recent decades. These strategies select inverter states in such a way that the common-mode voltage is reduced, thereby reducing leakage current. This work reviews space vector modulation techniques with reduced common-mode voltage for three-phase, two and three level inverters, using an LCLM filter. In addition, a commomode chock is added to the filter structure, ensuring that the leakage current is below the stipulated standard. Finally, it is proposed a new space vector modulation technique for three-phase three-level inverters.